Implementation of Criminal Law Against Cyberbullying on Social Media - Abdurrahman Harits Ketaren (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
Cyberbullying in Indonesia has become a serious concern in recent years, with the increasing use of digital technology such as social media and instant messaging applications as the main platform. This phenomenon not only includes various forms such as insults and threats, but also has a serious impact on the mental health of victims, including high levels of stress, anxiety, and depression. The ITE Law and the Criminal Code are the legal basis for dealing with cyberbullying, although their implementation still faces challenges in terms of consistency and effectiveness of law enforcement. Effective prevention strategies, such as education on digital ethics and increasing public awareness, are needed to reduce cyberbullying incidents in Indonesia. Active cooperation between the government, educators, technology platforms, and the community is key to creating a safe and supportive online environment for all technology users, especially the younger generation who are most vulnerable to the negative impacts of cyberbullying. Cybercrime will not occur if users have knowledge, awareness, especially students who should be more aware of the negative impacts on social media. Thus, it is necessary to conduct an analysis related to user awareness on social media.